Artificial intelligence-based large language models and integrity of exams and assignments in higher education: the case of tourism courses - Abdullah Ülkü (Tourism & Management Studies)
There is an increasing concern regarding the potential misuse of ChatGPT-4 in compromising the integrity of examinations and assignments. This study aims to examine the capabilities of ChatGPT-4 in critical thinking abilities, whether it poses a threat to examinations and assignments in higher education, and create a discussion agenda on this issue. ChatGPT-4 was asked to generate, answer, and criticize questions in tourism marketing, tourism management, tourism economics, tourist guidance, and gastronomy. The answers were evaluated according to universal critical thinking standards. The findings obtained from this study showed that ChatGPT-4 had commendable competence in several critical thinking standards and could produce human-like texts. However, there are certain domains that might be improved to comply more effectively with the expectations and norms of academia. Educators were recommended to use comprehensive approaches that combine technological and educational techniques to address the issue of cheating enabled by tools, such as ChatGPT-4, during assessment and exam processes.